2010
DOI: 10.1111/j.1745-4549.2009.00468.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Preharvest Treatment, Disinfection and Storage Environment on Quality of Carrots

Abstract: The physiological, microbiological and chemical quality changes were studied in carrots that received preharvest sprays of a commercial plant extract (ComCat) and subjected to disinfection and storage at 1 and 22C. At harvest, ComCat‐treated carrots had less aerobic and coliform bacteria population, higher contents of total available carbohydrates (TACs) and sucrose and lower glucose and fructose concentrations. During storage, ComCat‐treated carrots displayed reduced physiological weight loss (PWL) with lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…Hence, obtained data indicated that a combination of a 3% anolyte concentration at a 4 min dipping time could be retained as optimum for dates disinfecting treatment. This data confirmed the efficacy of active chlorine contained in electrolyzed water against naturally present microorganisms, as shown by Izumi (1999), on several fresh-cut vegetables (carrots, bell peppers, spinach, Japanese radish and potatoes), Bari et al (2003) on fresh tomatoes, Park et al (2008) on lettuce and spinach and by Workneh et al (2002) and Seyoum et al (2011) on carrots.…”
Section: Microbial Changessupporting
confidence: 86%
See 3 more Smart Citations
“…Hence, obtained data indicated that a combination of a 3% anolyte concentration at a 4 min dipping time could be retained as optimum for dates disinfecting treatment. This data confirmed the efficacy of active chlorine contained in electrolyzed water against naturally present microorganisms, as shown by Izumi (1999), on several fresh-cut vegetables (carrots, bell peppers, spinach, Japanese radish and potatoes), Bari et al (2003) on fresh tomatoes, Park et al (2008) on lettuce and spinach and by Workneh et al (2002) and Seyoum et al (2011) on carrots.…”
Section: Microbial Changessupporting
confidence: 86%
“…Previous studies by Izumi () and Seyoum et al . () also showed that the electrolyzed water led to maintain general sensory quality of fruits and vegetables, by reducing incidence of decay due to microbial activities. These results therefore demonstrated the importance of proper postharvest treatments to improve stored dates shelf life and maintain their quality.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…The decision to wash carrots before storage, or immediately before sale during the winter months is usually based on a farm's washing facilities and available labor and the storage conditions appled by carrot growers in Serbia quite often deviate from the optimal values in terms of both temperature and relative humidity [Ilić and Šunić 2015]. Combined effect of pre-and postharvest treatments has significant effect on maintaining postharvest quality and extension of carrot shelf life [Seyoum et al 2011]. Effects of prestorage treatments implying washing with addition of diverse agents on root vegetable shelf life were extensively investigated.…”
Section: Introductionmentioning
confidence: 99%